The Effectiveness of Community-Based Total Sanitation (STBM) Programs in Changing Clean and Healthy Living Behaviors - Junaidi; Aulia Rahmi Cheni; Widyastuti Harianto; Meci Miftahi Izati; Bunga (Knowledge and Environmental Science for Living and Global Health, 2025)
Community-based Total Sanitation (STBM) is a national approach to improving sanitation and public health through behavioral change. However, evidence on its effectiveness in shaping clean and healthy living behavior (PHBS) remains limited. Objective: This study evaluates the effectiveness of the STBM program in changing PHBS in a community intervention area. Methods: A mixed-methods design was applied. Quantitative data were collected from 150 respondents using pre- and post-intervention questionnaires and analyzed with paired t-tests. Qualitative data were obtained from in-depth interviews with community leaders and health workers and analyzed thematically. Results: Handwashing with soap increased from 58% to 82% (p < 0.01), the use of healthy latrines rose from 70% to 85% (p < 0.05), and household waste management improved from 62% to 76% (p = 0.06). Interviews revealed growing awareness of sanitation and environmental health, supported by active roles of health cadres and local leaders. Implications: These findings confirm that STBM is effective as a community-based strategy for behavior change, highlighting the importance of continuous education, participatory implementation, and integration with local development programs. Conclusion: STBM has a positive and significant impact on PHBS, and its sustainability depends on community participation and local government support.